The better brain book the best tools for improving memory and sharpness and preventing aging of the brain - Perlmutter, David 1954-; Colman, Carol (Tantor Audio, 2020)
From the author of the #1 New York Times bestseller Grain Brain and New York Times bestseller Brain Maker ... Loss of memory is not a natural part of aging-and this book explains why. Celebrated neurologist David Perlmutter reveals how everyday memory-loss-misplacing car keys, forgetting a name, losing concentration in meetings-is actually a warning sign of a distressed brain. Here he and Carol Colman offer a simple plan for repairing those problems, clarifying misconstrued connections between memory loss and aging, and regaining and maintaining mental clarity by offering the tools for: Building a better brain through nutrition, lifestyle changes, and brain workouts; Coping with specific brain disorders such as stroke, vascular dementia, Alzheimer's, Parkinson's, multiple sclerosis, and Lou Gehrig's disease; Understanding risk factors and individually tailoring a diet and supplementary program
Online resource; title from title details screen (OverDrive, viewed October 21, 2020)
Keywords: Memory disorders -- Prevention; Dietary supplements; Nootropic agents; Brain; Dietary Supplements; Nootropic Agents; Compléments alimentaires; Nootropiques; Cerveau; brains; SELF-HELP / General; Memory disorders; Prevention; Downloadable audio books; Audiobooks; Livres audio